IMPORTANCE OF RIDDLES IN LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In language learning process there are a great deal of factors so as to improve the language skills such as reading activities, writing activities, speaking activities, listening activities, crosswords, interactive games, conversations and others. As well as riddles has a vitally important role in this process.